Pentingnya Prosedur yang Disepakati dalam Teknik Lingkup Penugasan Audit Investigasi : (Studi Kasus Pada PT ABC) - Shalsya Dian Aprilyana; Gideon Setyo Budiwitjaksono (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Fraud is the deliberate and dishonest actions taken by someone to obtain unauthorized profits or benefits. Fraud can occur due to management manipulating financial statements by adjusting the company's profits. Investigative audits are used as an audit process carried out to investigate suspected fraud (fraud) violations of the law, or those problems that require in-depth examination. This study was conducted to explain and test how the agreed procedure process within the scope of an investigative audit can detect fraud. The object of this research is the company where the agreed procedure process is carried out. Interviews with auditors who handle or participate directly are carried out for data collection in the agreed procedure process. Data analysis produces secondary data from the interview process that has been carried out. This study produces an explanation that there are several tests used in the agreed procedure process within the scope of an investigative audit that are successful for detecting fraud in the company.